2000
DOI: 10.1074/jbc.275.15.10767
|View full text |Cite
|
Sign up to set email alerts
|

A G Protein-coupled Receptor for UDP-glucose

Abstract: Uridine 5-diphosphoglucose (UDP-glucose) has a well established biochemical role as a glycosyl donor in the enzymatic biosynthesis of carbohydrates. It is less well known that UDP-glucose may possess pharmacological activity, suggesting that a receptor for this molecule may exist. Here, we show that UDP-glucose, and some closely related molecules, potently activate the orphan G protein-coupled receptor KIAA0001 heterologously expressed in yeast or mammalian cells. Nucleotides known to activate P2Y receptors we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
292
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 318 publications
(307 citation statements)
references
References 23 publications
14
292
0
1
Order By: Relevance
“…On a speculative basis, UDP-Nacetylglucosamine and potentially UDP-galactose and UDPglucuronic acid may contribute to P2Y 14 R-dependent lung phenotypes. However, given the low P2Y 14 R agonist potency exhibited by these UDP-sugars, relative to UDP-glucose [13,54], UDP-glucose predictably is the most important autocrine/ paracrine regulator of P2Y 14 R-mediated lung inflammation. Recent studies examining P2Y 14 R-dependent second messenger formation in model cell lines revealed that UDP is a very potent agonist of this receptor [15].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On a speculative basis, UDP-Nacetylglucosamine and potentially UDP-galactose and UDPglucuronic acid may contribute to P2Y 14 R-dependent lung phenotypes. However, given the low P2Y 14 R agonist potency exhibited by these UDP-sugars, relative to UDP-glucose [13,54], UDP-glucose predictably is the most important autocrine/ paracrine regulator of P2Y 14 R-mediated lung inflammation. Recent studies examining P2Y 14 R-dependent second messenger formation in model cell lines revealed that UDP is a very potent agonist of this receptor [15].…”
Section: Discussionmentioning
confidence: 99%
“…The P2Y 14 R is a Gi-coupled receptor that is activated by UDP-sugars with a relative potency order of UDP-glucose > UDP-galactose > UDP-glucuronic acid > UDP-Nacetylglucosamine [13,14]. UDP also is an agonist of this receptor, but ATP, UTP, or other naturally occurring nucleoside 5′-di-or triphosphates have no P2Y 14 R activity [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, it has been shown that reducing the cellular level of UDP-GlcNAc to 5% of the normal level did not affect the synthesis or secretion of N-linked glycoproteins (58). Moreover, a G protein-coupled specific cell surface receptor for UDP-Glc, P2Y 14 , was recently identified (59,60), and the release of small amounts of UDP-Glc from a variety of cultured cells into the medium was demonstrated (61). UDP-Glc was postulated as a novel autocrine and paracrine signaling molecule, although the physiological processes regulated by its widely distributed receptor remain to be clarified.…”
Section: Fig 6 a Cellular Udp-glc Deficiency Does Not Cause Xbp-1 Amentioning
confidence: 99%
“…The most recently identified subtypes are the P2Y 13 receptor, which is present in human monocytes and lymphocytes, 42 and the P2Y 14 receptor, which is activated by UDP-glucose. 43 P2Y receptor ligands are being investigated for therapeutic applications in the cardiovascular, endocrine, and other systems. Exploration of selective agonists and antagonists modulators is most advanced at the P2Y 1 and P2Y 12 receptors, but at most of the P2Y receptors selective pharmacological probes are lacking.…”
Section: Discussionmentioning
confidence: 99%